Enhancing the QoS performance for mobile station over LTE and WiMAX networks / Mhd Nour Hindia - Hindia, Mhd Nour (2015)
Nowadays, one of the most important challenges in heterogeneous networks is the connection consistency between the mobile stations and base stations while maintaining a high degree of quality of service. Furthermore, along the roaming process between the mobile station and the base station, the system performance degrades significantly due to interferences from neighboring base stations, handovers to inaccurate base station, inappropriate technology selections and insufficient scheduling schemes. In this study, several algorithms are proposed to guarantee high efficiency of resource allocations among a variety of smart grid applications (flat priority based and specific priority based scheduling algorithms), such as distribution automation, voice, video surveillance and advanced metering infrastructure. These algorithms can improve mobile stations’ quality of service as well as guarantee seamless mobility across the Long-Term Evolution (LTE) and Worldwide Interoperability for Microwave Access (WiMAX) technologies. Firstly, to solve the handover issues (prediction target base station, and selection best target technology), the enhanced global positioning system (GPS) and the novel received signal strength (RSS) prediction algorithms are utilized to accurately predict the target base station. Then, a multi criteria with two-threshold algorithm is proposed to prioritize the selection between the LTE and WiMAX as target technologies. In addition, this thesis also covers the inter-cell and co-channel interference reduction by adjusting the frequency reuse ratio 3 (FRR3) to work with LTE and WiMAX. Moreover, in terms of flat priority based scheduling issues, this thesis proposes a two level scheduling scheme composed of cooperative game theory (bankruptcy and shapely) and Technique for Order Performance by Similarity to Ideal Solution method (TOPSIS). On the first level, bankruptcy and shapely value algorithm fairly distribute resources among smart grid applications. On the second level, TOPSIS algorithm allocates resources among an application’s user based on their criteria and the application’s preferences. The proposed algorithms provide an effective scheduling technique for smart grid applications. Whereas for specific priority based scheduling issues, the bandwidth estimation and allocation along with multi-attributes decision making are proposed. The results obtained show that in terms of handover issues, a modified multi criteria with two threshold algorithm increases the efficiency of target network selection. The selection is based on the user preferences since it uses a self-learning algorithm to determine triggers and handover thresholds dynamically. In addition, by adding the FRR3 technique to the system, the efficiency of prediction of target base station and selection of target technology are increased, and the delay is decreased by approximately 15%. Similarly, in terms of flat priority based scheduling issues, the proposed algorithm also is found to be of higher performance up to 42 users for video applications and 60 users for the metering data applications. Finally, the novel algorithm shows the lowest delay and the highest fairness of approximately 0.98 whereas for specific priority based scheduling issues, the simulation results demonstrate that the proposed mechanism achieves higher throughput, lower delay and lower packet loss rate for real time applications as well as provides a degree of service for non-real time applications. In terms of fairness, the proposed algorithm shows 3%, 7 % and 9% better performance compared to exponential rule, modified-largest weighted delay first and exponential/proportional fairness, respectively.